(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2025)
The purpose of this article is to reflect on the relationship between human subjects and technological devices through two artistic installations: Máquina Cóndor (2006-ongoing) and Máquina de Coser (2009-ongoing), by Chilean visual artist Demian Schopf, through the critical perspective of new materialisms. By means of a brief theoretical journey that addresses the studies of Walter Benjamin (1936, 1983), Jane Bennett (2010), Jusi Parikka (2012, 2021), Manuel de Landa (2021), among others, I propose that Schopf’s works are constitutive of a poetics of assemblage, in which the frictions between organic bodies and technological devices propitiates the configuration of a complex human-machinic framework. As a methodology, I examine two discursive procedures of the works that establish this configuration: writing and dialogue, poetic mechanisms made possible by artificial intelligence.